Opportunities to enhance ward audit: a multi-site qualitative study - Michael Sykes; Richard Thomson; Niina Kolehmainen; Louise Allan; Tracy Finch (BMC, 2021)
Abstract Background Hospitals in many countries are encouraged to develop audits to assess and improve the quality of care. Ward audit is a specific form of audit and feedback that is commonly used but little studied. The aim of this study is to describe the content and application of hospital ward audit in order to identify potential enhancements to such audits. Methods Multiple qualitative methods were used to study a diversity sample of four English National Health Service organisations over a 16-month period. We undertook semi-structured interviews (n = 32), documentary analysis (n = 44) and 25 h of observations of healthcare workers involved in the design and implementation of ward audit. Data were analysed using framework analysis. Findings were presented iteratively to stakeholders who used them to develop a description of the content and delivery of ward audit. Results Ward audit consisted of seven stages: impetus; method; preparation of staff; assessing practice; analysis; feedback; and decide on action to improve. Two key stages were the monthly assessment of practice using case note data extraction, and the resulting feedback to clinical staff, ward managers, matrons and directors of nursing. At three organisations, the case note data were extracted by staff and there was evidence that this resulted in misrepresentation of the clinical performance audited. The misrepresentation appeared to be associated with the anticipation of punitive feedback from directors of nursing and matrons, as well as time pressures and a lack clarity about the method of audit data collection. Punitive feedback was reported to occur if no data were collected, if data demonstrated poor performance or if performance did not improve. Conclusions Organisations invest considerable clinical resources in ward audit, but such audits may have unintended, potentially negative, consequences due to the impacts from punitive feedback. We discuss potential enhancements to ward audit (e.g. providing feedback recipients with suggested actions for improvement) and discuss implications for theory. There is a need to reduce the use of punitive feedback.